(untitled) (South East Asia Journal of Public Health, 2013)
Trials have demonstrated improvement in patients quality of life through palliative care services (PCS). However, many of these trials are limited by their research methodologies. PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL) were searched to conduct a systematic review of review articles related to PCS from January 2001 to December 2011. The paper examined evidence from studies on PCS that aimed to improve elderly patients end-of-life outcomes by i) systematically reviewing literature on models of palliative care (PC) delivery patients received; ii) exploring methodological issues surrounding recruitment of the patients, implementation of the studies and comparison of health care services; and iii) addressing the costs of care with/without a palliative program. Seventeen trials and three observational studies were selected from nine systematic review articles. Overall, early introduction of PC to patients following identification of their life-limiting conditions and needs re-quires an organized and coordinated care approach to ensure accessibility of these services. The ideal system that offers the potential of improving patients quality of life is one that is integrated, interdisciplinary and holistic. Dying is commonly institutionalized; however, providing outreach programs that allow patients to die at their place of wish, such as domiciliary care, offers the potential of addressing the issue of ever-increasing health-care expenditure for the aged. However, further investigation is needed to evaluate the cost effectiveness of these programs. Methodological problems and ethical issues surrounding the study of terminally-ill patients necessitate that researchers use a combination of observational studies and surveillance system over time. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15937 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 5-15